Pengaruh Ekspor, Impor, dan Kurs terhadap Pertumbuhan Ekonomi di Indonesia - Putra, Faqih Alamsyah (GROWTH Jurnal Ilmiah Ekonomi Pembangunan, 2022)
The topic discussed in this research is the effect of exports, imports and exchange rates on Economic Growth in Indonesia. The data used in this study is secondary data obtained from the World Bank in 1999-2020. The analysis used is the Error Correction Model (ECM) method. The test uses the Stationarity Test, Cointegration Test, and Classical Assumption Test models. The result of the research is that in the long run, the variables of exports and imports affect economic growth, while the exchange rate has no effect on economic growth. In the short term, only imports affect economic growth, while the other two variables, namely exports and exchange rates, don’t affect economic growth.